Cerebrospinal fluid FGF23 levels correlate with a measure of impulsivity. (June 2018) - Li, Hui; Cao, Zhiyong; Xu, Jinzhong; Wang, Fan; Xiong, Rongrong; Xu, Zeping; Luo, Xianming; Li, Guohua; Tan, Xingqi; Liu, Zhiyang; Gao, Zhiqin; Kang, Yimin; et al.
Highlights: CSF FGF23 levels ranged from 12.8 to 99.3 pg/mL. Negative correlations were found between CSF FGF23 concentrations and BIS Nonplanning, BIS Cognition and BIS Total scores (all p  < 0.05). No correlations were found between CSF FGF23 concentrations and BDI or SAS scores. Abstract: Fibroblast growth factor 23 (FGF23) is a bone-derived protein produced mainly by osteocytes and osteoblasts and at low levels in specific parts of the brain. It has been shown to associate with mood regulation. Lithium treatment gives rise to significant elevations of serum FGF23 levels in depressive patients. High peripheral blood FGF23 levels correlated with poor cognitive performance in hemodialysis patients. However, no direct evidence demonstrates a relationship between FGF23 and mood regulation. In this study, we aimed to measure the concentration of cerebrospinal fluid (CSF) FGF23 and to explore its relationship with a cluster of emotional characteristics. We measured CSF FGF23 levels in 96 male Chinese subjects. All subjects completed the Chinese version of the Barratt Impulsiveness Scale (BIS 11), the Beck Depression Inventory (BDI) and the Self-Rating Anxiety Scale (SAS). CSF FGF23 levels ranged from 12.8 to 99.3 pg/mL. Negative correlations were found between CSF FGF23 concentrations and BIS non-planning, BIS cognition and BIS total score (all p  < 0.05). Nevertheless, except for the BIS cognition scores, these correlations became insignificant after Bonferroni correction. No correlations were found between CSF FGF23 concentrations and BDI or SAS scores. These findings suggest that CSF FGF23 levels correlate with a measure of impulsivity.